Réponses

Meilleure réponse !
  • Utilisateur Brainly
2013-11-14T19:11:19+01:00
A = 3/5 - 2/7  divisé par 5/7  
=3/5-2/7x7/5
=3/5-2/5
=1/5

B = (3-2/9) x (3 divisé par  2/9)  
=25/9x27/2
=675/18

C = -2/3 x 1/4 - 2/7 divisé par 12/5
=-1/6-2/7x5/12
=-1/6-5/42
=-2/7 

2013-11-14T19:30:36+01:00
A = 3/5 - 2/7 :5/7 
=3/5-2/7 x 7/5
=3/5-2/5
=1/5

B = (3-2/9) x (3 : 2/9) 
=(27/9-2/9) x (3 x9/2)
=25/9 x 27/2
=25/1 x 3/2
=75/2

C = -2/3 x 1/4 - 2/7 :12/5
=-1/3 x 1/2- 2/7 x 5/12
=-1/6 - 1/7 x 5/6
=-1/6 - 5/42
=-7/42-5/42
=-12/42
=-4/14
=-2/7